PEMBELAJARAN MAHFUDZOT DI PONDOK PESANTREN AL-BASYARIYAH DALAM TELAAH TEORI PEMROSESAN INFORMASI (ATKINSON DAN SHIFFRIN) - Rojab, Taufik (Universitas Nahdlatul Ulama Pasuruan, 2023)
The Information Processing Theory proposed by Atkinson and Shiffrin emphasizes the interaction between sensory storage, short-term memory, and long-term memory. This study aims to describe the application of information processing theory (Atkinson and Shiffrin) to Mahfudzot learning at Al-Basyariyah Islamic Boarding School. This study uses a qualitative approach. Data analysis is focused on reading, studying, and reviewing books and written sources that are closely related to the problems discussed, based on document analysis, namely the Tarbiyah Amaliyah book that learning mahfudzot at Al-Basyariyah Islamic Boarding School applies the theory of memory developed by Atkinson and Shiffrin which is a branch from Information Processing Theory, namely with three stages; sensory memory stage, short term memory, long term memory